2014
DOI: 10.1177/0004867414540752
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-month prevalence and predictors of self-reported suicidal ideation and suicide attempt among Korean adolescents in a web-based nationwide survey

Abstract: A multidisciplinary approach that takes into consideration the characteristics of Korean adolescents with suicidal ideation or suicide attempt is warranted for developing prevention and treatment programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 28 publications
(36 reference statements)
7
42
3
1
Order By: Relevance
“…Female sex and living in urban areas was associated with increased odds of suicidal behavior, which has similarly been found among South Korean adolescents [21,22,23]. Furthermore, also consistent with the results from South Korean adolescents, we found that living without families [21] and low socio-economic status [23] were risk factors, suggesting that a lack of social resources might increase the risk of suicidal behaviour.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Female sex and living in urban areas was associated with increased odds of suicidal behavior, which has similarly been found among South Korean adolescents [21,22,23]. Furthermore, also consistent with the results from South Korean adolescents, we found that living without families [21] and low socio-economic status [23] were risk factors, suggesting that a lack of social resources might increase the risk of suicidal behaviour.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, also consistent with the results from South Korean adolescents, we found that living without families [21] and low socio-economic status [23] were risk factors, suggesting that a lack of social resources might increase the risk of suicidal behaviour. Perceived academic performance was also related: students with high or low academic achievement tended to have a higher risk than did those with a middle level of achievement, which has also been found in a sample of South Korean adolescents [23]. This is perhaps because students who perceive that their academic performance deviates from the average might experience higher academic stress, and might be under pressure either to maintain their excellent results or to catch up with their peers.…”
Section: Discussionsupporting
confidence: 88%
“…For instance, in the US, approximately 538,000 suicide attempts were reported every year between 2005 and 2008 [14]. In South Korea, a web-based anonymous self-reported survey with 72,623 adolescents aged 12-18 years revealed that the prevalence of suicide attempts was 4.9% in the past 12 months [15]. China has the largest population in the world, as well as containing the largest adolescent population.…”
Section: Introductionmentioning
confidence: 99%
“…The suicide rate in adolescents has been rising rapidly. According to the result of sixth Korea Youth Risk Behavior Web-based Survey, 19.1% of the total participants (72,623 of total adolescents aged 13~18years old) had experienced suicidal ideation and 4.9% actually attempted suicide [2]. The probability of death resulting from a suicidal act is 100 times higher in the attempters than in the general population [3].…”
Section: Introductionmentioning
confidence: 99%